Proposed Educational Requirements to Activate the Strategy of Individualizing Education in Jordanian Public schools in Light of Coronavirus Pandemic - Alabed, Mjdwlyn Zuheir Muhammad; Alabed , Roweida Zuheir Muhammad (Dirasat: Educational Sciences, 2022)
Objectives: This study aims to build educational requirements to activate the strategy of individualizing education in Jordanian public schools in light of the Coronavirus pandemic. Methods: A developmental survey was used. The study population consisted of all public school teachers in Jordan. The study sample amounted to (500) male and female teachers for the academic year (2021/2020). Results: The results of the study show that the degree of importance of practicing the strategy of individualizing education at Jordanian public schools in light of the Coronavirus pandemic in general was high. The results also indicated that there were differences in gender in favor of males, and differences in educational qualification in favor of graduate degrees. Conclusions: The study recommends organizing qualifying training courses for teachers, students and others working in the educational field. These courses should be concerned with activating modern methods of teaching, especially the strategy of individualizing education to achieve the desired educational and educational goals in light of the Coronavirus pandemic. The study also recommends using educational platforms to hold qualifying and training courses specialized in activating the strategy of individualizing education. The study also recommends inviting decision-makers in the Jordanian Ministry of Education to adopt the educational requirements proposed here to activate the strategy of individualizing education.